Study on Ultimate Compressive Strength of Aluminium-Alloy Plates and Stiffened Panels - Liu, Bin; Doan, Van Tuyen; Garbatov, Y.; Wu, Weiguo; Guedes Soares, C. (Journal of marine science and application, 2020)
This work reviews the ultimate compressive strength of aluminium plates and stiffened panels. The effect of boundary condition, initial imperfection, welding-induced residual stress and heat-affected zone are discussed. As the effect of manufacturing technology lacks in the literature, this effect is analysed employing the finite element method, considering the technology of welding and integrated extrusion. The numerical analyses have shown that the ultimate strength of the integrated extruded stiffened panel is relatively higher than the one of the traditional welded panel.